KONSTRUKTIVISME DALAM PENDIDIKAN AGAMA ISLAM TINJAUAN FILOSOFIS TERHADAP PEMBELAJARAN AKTIF - Fakrijal Fakrijal (NIHAYAH: Journal of Islamic Studies, 2025)
Islamic Religious Education (IRE) has long been dominated by expository and teacher-centered approaches, which often result in weak critical thinking and insufficient internalization of Islamic values among students. This article aims to examine constructivism as an alternative pedagogical approach that promotes active, reflective, and meaningful learning in the context of IRE, through a philosophical lens grounded in Islamic education thought. This study employs a qualitative method with a library research model using descriptive-analytical and philosophical approaches. Data were collected from books, academic journal articles, and relevant and analyzed using hermeneutic interpretation and conceptual triangulation. The findings indicate that constructivist approaches in IRE empower students as active subjects in constructing their understanding of religious knowledge through experience, social interaction, and personal reflection. Strategies such as discussion, case studies, simulations, and project-based learning are proven to enhance critical thinking, contextual comprehension, and the application of Islamic ethics. Philosophically, constructivism aligns with the Islamic principles of tafakkur (contemplation), tadabbur (reflection), and the integration of intellectual and spiritual development. In conclusion, constructivism not only offers an effective pedagogical method but also supports the transformative vision of IRE in nurturing faithful, critical, and socially engaged individuals. Teacher training, curriculum development, and further research are recommended to strengthen the implementation of constructivist approaches in Islamic education.